Transcriptome analysis of Actinidia chinensis in response to Botryosphaeria dothidea infection - Wang, Yuanxiu (PLoS One, 2020)
Ripe rot caused by Botryosphaeria dothidea causes extensive production losses in kiwifruit (Actinidia chinensis Planch.). Our previous study showed that kiwifruit variety “Jinyan” is resistant to B. dothidea while “Hongyang” is susceptible. For a comparative analysis of the response of these varieties to B. dothidea infection, we performed a transcriptome analysis by RNA sequencing. A total of 305.24 Gb of clean bases were generated from 36 libraries of which 175.76 Gb was from the resistant variety and 129.48 Gb from the susceptible variety. From the libraries generated, we identified 44,656 genes including 39,041 reference genes, 5,615 novel transcripts, and 13,898 differentially expressed genes (DEGs). Among these, 2,373 potentially defense-related genes linked to calcium signaling, mitogen-activated protein kinase (MAPK), cell wall modification, phytoalexin synthesis, transcription factors, pattern-recognition receptors, and pathogenesis-related proteins may regulate kiwifruit resistance to B. dothidea. DEGs involved in calcium signaling, MAPK, and cell wall modification in the resistant variety were induced at an earlier stage and at higher levels compared with the susceptible variety. Thirty DEGs involved in plant defense response were strongly induced in the resistant variety at all three time points. This study allowed the first comprehensive understanding of kiwifruit transcriptome in response to B. dothidea and may help identify key genes required for ripe rot resistance in kiwifruit.